Systematic Review of Telehealth Cost Minimization for Patients and Health Systems in Otolaryngology. (23rd December 2020) - Cabrera, Claudia I.; Ning, Anne Y.; Cai, Yida; D'Anza, Brian
Abstract : Objective/Hypothesis: The COVID‐19 pandemic has resulted in telehealth becoming commonplace in many health care fields. Telehealth benefits include improving access, decreasing costs, and elevating patient's experience. A review of cost minimization (CM) analyses was performed in order to explore scientific studies associated with integrating tele‐otolaryngology in clinical practice. Our primary objective was to evaluate published literature for cost related to the implementation of telemedicine across otolaryngology, and to determine CM when compared to in‐person visits. Study Design: Systematic Literature Review. Methods: We performed a systematic review using PubMed, EMBASE, and Cochrane in May 2020, to identify studies with a cost analysis of tele‐otolaryngology care. Inclusion criteria focused on articles citing CM data from telehealth services. Literature quality was assessed using the MINORS scoring system. Results: From 380 original articles screened only nine evaluated cost in otolaryngology. CM in the US ranged from $68 to $900 per visit. Cost was evaluated in general otolaryngology, sleep medicine, otology, and head and neck cancer surgery, the latter had the most benefit. The most common types of telehealth visits were routine follow‐up and screening. Data were insufficient for meta‐analysis. Conclusions: Telemedicine has been trialed across various otolaryngology subspecialties; its incorporation is projected to have a meaningful impact on access to specialty care. This research suggests that the delivery of virtual care reduces cost with the potential of increasing net revenue across multiple otolaryngology subspecialties. Further studies are needed to better discern the entirety of cost savings and the best settings for integration. Level of Evidence: 3 Laryngoscope, 131:1741–1748, 2021